Circulating and Salivary Antibodies to Fusobacterium nucleatum Are Associated With Cystic Pancreatic Neoplasm Malignancy - Alkharaan, Hassan; Lu, Liyan; Gabarrini, Giorgio; Halimi, Asif; Ateeb, Zeeshan; Sobkowiak, Michał J.; Davanian, Haleh; Fernández Moro, Carlos; Jansson, Leif; Del Chiaro, Marco; Özenci, Volkan; Sällberg Chen, Margaret (Frontiers in Immunology, 2020)
Objectives Intraductal papillary mucinous neoplasms (IPMNs) are cystic precursor lesions to pancreatic cancer. Presence of oral microbes in pancreatic tissue or cyst fluid has been associated with high-grade dysplasia and cancer. The present study aims at investigating if humoral immunity to pancreas-associated oral microbes reflects IPMN severity. Design Paired plasma (n=109) and saliva (n=65) samples were obtained from IPMN pancreatic cystic tumor cases and controls, for anti-bacterial antibody analysis and DNA quantification by ELISA and qPCR, respectively. Tumor severity was graded by histopathology, laboratory, and clinical data. Circulating plasma and salivary antibody reactivity to a pancreas-associated oral microbe panel were measured by ELISA and correlated to tumor severity. Results The patient group with high-risk cystic tumors (high-grade dysplasia and/or associated invasive cancer) shows ample circulating IgG reactivity to Fusobacterium nucleatum (F. nucleatum) but not to Granulicatella adiacens (G. adiacens), which is independent of the salivary bacteria DNA levels. This group also shows higher salivary IgA reactivity to F. nucleatum, Fap2 of F. nucleatum and Streptococcus gordonii (S. gordonii) compared to low-risk IPMN and controls. The salivary antibody reactivity to F. nucleatum and Fap2 are found to be highly correlated, and cross-competition assays further confirm that these antibodies appear cross-reactive. Conclusions Our findings indicate that humoral reactivity against pancreas-associated oral microbes may reflect IPMN severity. These findings are beneficial for biomarker development.